The expression pattern of butyric acid transporter in the large intestine with growth and development of suckling lambs - Jian Ma; Tao Li; Lu Lin; Chunmei Du; Chen Wei; Fuquan Yin; Xuemei Sun; Gang Lyu; Shangquan Gan (Animal Bioscience)
Objective The objective of this research was to explore the changes of morphological parameters, short chain fatty acid contents and butyric acid transporter expression levels in the large intestine with growth and development of sucking lambs. Methods A total of 48 newborn male Hu sheep lambs (body weight = 2.94±0.22 kg) were selected in this experiment. At 0, 7, 14, 28 and 42 days of ages, 6 lambs were slaughtered to collect cecal and colonic samples to analyze morphological parameters, short chain fatty acid contents and butyric acid transporter mRNA expression. Results The organ index of the cecum in d 0, 28 and 42 groups was higher (p<0.05) than that in d 7 and 14 groups. Compared with other age groups, the organ index of the colon was significantly increased (p<0.05) in d 42 group. After 7 days of age, the contents of acetic, propionic and butyric acids in the cecum and colon were significantly increased (p<0.05) as age increased. A similar trend of mRNA expressions of butyric acid transporters, including monocarboxylate transporter, sodium-coupled monocarboxylate transporter, sodium-hydrogen exchanger, down regulated in adenoma, putative anion transporter-1 and anion exchanger-2, was found. In the cecum, the Escherichia coli count in d 14 group was higher (p<0.05) than that in other age groups, whereas an opposite tendency was found in Lactobacillus count between d 14 and other groups. Additionally, in the cecum and colon, the relative expression of claudin-1 in d 14 group was lower (p<0.05) than in d 42 group. Conclusion Overall, the current results indicate that the expression levels of butyric acid transporters in the cecum and colon of lambs are significantly influenced by days of age.